Diskursus Uqubat Cambuk dalam Qanun Jinayat Aceh: Antara Efektivitas Hukum dan Kritik HAM Internasional - Fitra Ardiansyah; Muhammad Ramadhana; Hanif Rahman Adyaksa Tambunan; Fairuz Amanina; Fitri Amanda Hasibuan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research critically examines the implementation of flogging punishment as regulated in Qanun Jinayat Aceh, particularly from the perspective of legal effectiveness and its challenges to international human rights principles. As the only region in Indonesia that formally implements Islamic criminal law, Aceh has become a focal point in both national and global legal discourse. Utilizing a normative qualitative approach and juridical-philosophical analysis of the qanun regulations, field practices, and criticisms from international institutions such as Komnas HAM and Human Rights Watch, the findings indicate that although uqubat flogging is considered effective in creating a deterrent effect and enjoys social legitimacy in parts of Acehnese society, its implementation remains highly controversial, particularly regarding respect for human dignity, fair trial mechanisms, and universal human rights protection standards. This study emphasizes the need for a more humanistic, contextual, and socially responsive approach without disregarding the basic principles of Islamic law, with the expectation that this discourse will enrich the treasury of Islamic legal thought and encourage the reformulation of sharia criminal law in line with substantive justice values.